2021
DOI: 10.1108/jhr-07-2020-0244
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perceptions of COVID-19 self-protective measures: a structural equation modeling (SEM) approach

Abstract: PurposeThis study aimed to develop scales to assess perceptions of coronavirus disease 2019 (COVID-19) self-protective measures (SPMs) and examine the psychometric properties based on the theory of planned behavior (TPB).Design/methodology/approachA total of 412 participants from Bangalore, India, randomly volunteered to participate in this research. The questionnaire consisted of items related to the TPB scales and demographic details.FindingsA structural equation model showed a reasonable model fit. In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
4
0
4
Order By: Relevance
“…Next, HS-capacity is impacted through the collective self-efficacy of the population who feel to have the abilities to stay healthy when they perceive the HS-capacity is collapsing. This is confirmed by the literature that found conceptual direct linear relations between HS-capacity and public administration [9,14,35,[40][41][42][43][44], preparedness [6,7,35,45], information [38,39,[46][47][48], or collective self-efficacy [14,41,49,50].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Next, HS-capacity is impacted through the collective self-efficacy of the population who feel to have the abilities to stay healthy when they perceive the HS-capacity is collapsing. This is confirmed by the literature that found conceptual direct linear relations between HS-capacity and public administration [9,14,35,[40][41][42][43][44], preparedness [6,7,35,45], information [38,39,[46][47][48], or collective self-efficacy [14,41,49,50].…”
Section: Discussionsupporting
confidence: 77%
“…Common method bias is a potential problem here as our data are gathered in a self-completed survey. A Harman’s single-factor test was used on items selected by EFA with no rotation and results were compared against the threshold of 0.50 [ 50 ]. This resulted in one factor explaining 30.76%, 30.38%, 45.80% of the total variance for Bolivia, Nicaragua, and Uruguay, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bok et al (2021), that Perceived Benefits are the driving force that influences people's attitudes towards the use of medical masks during the COVID-19 pandemic, which ultimately determines their intention to use them continuously. The results of the study of Mehrolia et al (2021), found that consumers feel that when using a medical mask, they can protect themselves from contracting disease and avoiding illness due to COVID-19. This perception will develop a positive attitude towards it, and they will like to use it continuously.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…Di antaranya adalah persepsi norma sosial (perceived social norms) dan juga persepsi pengaruh sosial (perceived social influence). Karenanya menurut Brewer et al (2017) penelitian substansial telah menunjukkan bahwa norma-norma sosial memiliki pengaruh dan keterkaitan dengan minat vaksinasi di antaranya pada penelitian (Mehrolia et al, 2021;Quinn et al, 2017;Vet et al, 2011). Sedangkan berkaitan dengan persepsi pengaruh sosial, Ni et al (2021) (Avkiran, 2018).…”
Section: Pendahuluanunclassified